PENGARUH UKURAN PERUSAHAAN, LEVERAGE, KEBIJAKAN DIVIDEN, KEPEMILIKAN INSTITUSIONAL DAN KEPEMILIKAN MANAJERIAL TERHADAP MANAJEMEN LABA (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2010-2013) - Pratama, Muhammad Yogi; Hasan, Amir; Diyanto, Volta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This research aims to analyze and gets empirical prove of size of company, leverage, dividend policy, institutional ownership and managerial ownership on earnings management. The population in this research were manufacturing sector companies listed on the Indonesian Stock Exchange (IDX) year period from 2010 to 2013. Purposive sampling method is used to determine the sample, while the data processing methods used are multiple regression analysis by using SPSS version 17.0 as the software for processing data. With the sampling method, it is found samples as many as 80 companies that were used in this study. The results prove that size of company, dividend policy, institutional ownership, managerial ownership has no signicant effect on earnings management, this is indicated from its significance value more than 0.05. While leverage has a significant effect on earnings management significantly by 0.005.Keywords: Eearnings management, size of company, leverage, dividend policy and good corporate governance